Damaged [compact disc, unabridged] : a Maggie O'Dell novel - Kava, Alex (Kava, Alex. Maggie O'Dell series., 2010)
On Pensacola Beach, the Coast Guard prepares for a Category 5 hurricane. Patrolling the waterways, they spot a huge fishing cooler about a mile offshore. Drug traffickers have been known to dump coolers with smuggled product to avoid detection and pay fishermen to retrieve them. But when the crew opens this cooler, they're shocked to find body parts tightly wrapped in plastic. Though she is putting herself in the projected path of the hurricane, Special Agent Maggie O'Dell investigates.